Novel 2-substituted-benzimidazole-6-sulfonamides as carbonic anhydrase inhibitors: synthesis, biological evaluation against isoforms I, II, IX and XII and molecular docking studies - Ciro Milite; Giorgio Amendola; Alessio Nocentini; Silvia Bua; Alessandra Cipriano; Elisabetta Barresi; Alessandra Feoli; Ettore Novellino; Federico Da Settimo; Claudiu T. Supuran; Sabrina Castellano; Sandro Cosconati; et al. (Taylor & Francis Group, 2019)
Inhibition of Carbonic Anhydrases (CAs) has been clinically exploited for many decades for a variety of therapeutic applications. Within a research project aimed at developing novel classes of CA inhibitors (CAIs) with a proper selectivity for certain isoforms, a series of derivatives featuring the 2-substituted-benzimidazole-6-sulfonamide scaffold, conceived as frozen analogs of Schiff bases and secondary amines previously reported in the literature as CAIs, were investigated. Enzyme inhibition assays on physiologically relevant human CA I, II, IX and XII isoforms revealed a number of potent CAIs, showing promising selectivity profiles towards the transmembrane tumor-associated CA IX and XII enzymes. Computational studies were attained to clarify the structural determinants behind the activities and selectivity profiles of the novel inhibitors.